Answer:
y + 1 = 3( x + 1)
Step-by-step explanation:
We are asked to find the equation of the line in point-slope form
Step 1 : find the slope using the two points given
( 0 , -3) ( 2,3)
m = (y_2 - y_1) / (x _2 - x_1)
x_1 = 0
y_1 = -3
x_2 = 2
y_2 = 3
Insert the values into
m = 3 - (-3) / 2 - 0
m = 3 +3 / 2 - 0
= 6/2
= 3
Step 2: it was given in the question that the parallel to a given line and passes through ( -1 , -1)
Substitute the point into the equation
y - y_1 = m ( x - x _1)
m = 3
y - y_1 = 3 ( x - x_1)
x_1 = -1
y_1 = -1
y - (-1) = 3( x - (-1)
y +1 = 3 ( x + 1)
We don't need to open the bracket because we are asked to give the answer in a point-slope form
The equation of the line in point slope form is
y + 1 = 3( x + 1)